Chemokines: A Potential Therapeutic Target to Suppress Autoimmune Arthritis - Khan, Mahmood A.; Khurana, Nikhil; Ahmed, Rafat S.; Umar, Sadiq; Md. G. Sarwar, Abu H.; Alam, Qamre; Kamal, Mohammad A.; Ashraf, Ghulam M. (Current Pharmaceutical Design, 2019)
Background: Chemokines are a family of low molecular weight proteins that induce chemotaxis of inflammatory cells, which mainly depends on the recognition of a chemo-attractant gradient and interaction with the substratum. In Rheumatoid Arthritis (RA), abundant chemokines are expressed in synovial tissue, cause inflammatory cells migration into the inflamed joint that necessitates the formation of new blood vessels i.e. angiogenesis. Over the decades, studies showed that continuous inflammation may lead to the loss of tissue architecture and function, causing severe disability and cartilage destruction. In spite of the advancement of modern drug therapy, thousands of arthritic patients suffer mortality and morbidity globally. Thus, there is an urgent need for the development of novel therapeutic agents for the treatment of RA. Methods: This review is carried out throughout a non-systematic search of the accessible literature, will provide an overview of the current information of chemokine in RA and also exploring the future perspective of the vital role of targeting chemokine in RA treatment. Results: Since, chemokines are associated with inflammatory cells/leucocyte migration at the site of inflammation in chronic inflammatory diseases and hence, blockade or interference with chemokines activity showing a potential approach for the development of new anti-inflammatory agents. Currently, results obtained from both preclinical and clinical studies showed significant improvement in arthritis. Conclusion: This review summarizes the role of chemokines and their receptors in the pathogenesis of RA and also indicates possible interactions of chemokines/receptors with various synthetic and natural compounds that may be used as a potential therapeutic target in the future for the treatment of RA.
Keywords: Rheumatiod arthritis